Analisis Kesalahan dalam Menyelesaikan Soal Cerita Matematika Ditinjau dari Sikap Belajar Siswa Kelas VII SMPN 15 Mataram - Syahril Ramdhan; Nani Kurniati; Tabita Wahyu Triutami; Syahrul Azmi (FKIP Universitas Mataram, 2024)
The aim of this research is to analyze student errors in solving word problems in terms of learning attitudes in class VII students at SMPN 15 Mataram in the 2023/2024 academic year using the Newman procedure. This type of research is descriptive qualitative. The sample used was 30 people from class VII-B with the sampling technique used was purposive sampling with data collection techniques carried out by tests, questionnaires and interviews. The results showed that students with a high learning attitude, with a total of 3 students, made 11.11% errors in Comprehension Errors, 22.22% transformation errors, 27.78% process skill errors, and 61.11% encoding errors. . Students with moderate learning attitudes, numbering 23 students, made errors in reading errors as much as 15.21%, Comprehension Errors as much as 31.88%, transformation errors as much as 44.92%, process skill errors as much as 62.31%, and encoding errors as much as 57.98%. Students with low learning attitudes, with a total of 4 students, made errors in reading errors as much as 25%, Comprehension Errors as much as 29.16%, transformation errors as much as 50%, process skill errors as much as 62.5%, and encoding errors as much as 100%. The causes of students making mistakes are weak understanding of concepts, limited ability to read and understand questions, lack of problem solving strategies, lack of practice and experience, and lack of self-confidence.